Suplementasi Probiotik Limbah Pertanian untuk Meningkatkan Produktivitas Ternak Sapi - Tinda Afriani; Mangku Mundana; Adisti Rastosari; Moch. Evan Setiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Probiotics are microorganisms that are beneficial to the host and can improve the intestine's microflora. For ruminants in Indonesia, high numbers of cellulolytic microorganisms are needed to utilize forage or agricultural waste as efficiently as possible in producing the nutrients needed by livestock. Therefore, a feed additive is needed to improve the rumen function's performance, and one of them is probiotics. Solid and liquid probiotics have several advantages, namely containing live microbial cultures that are desirable and beneficial for livestock through increasing the balance of digestive microbes and playing a role in providing enzymes that can digest crude fibre and lactic acid bacteria. Probiotics also can produce anti-microbial ingredients (bacteriocins) to inhibit the growth of unfavourable microbes. The use of microorganism supplements (probiotics) has been socialized in the Nagari Ampang Pulai, Koto XI Tarusan District, and Pesisir Selatan Regency. The efficiency of using agricultural waste probiotics in cattle rations as much as 10 ml/head/day is expected to increase body weight gain by 0.70 kg/head/day, according to an experiment at the Faculty of Animal Husbandry, Andalas University. In general, liquid probiotics are more effective as feed additives when compared to solid probiotics in rice straw and concentrate-based rations.